Associations between deployment, military rank, and binge drinking in active duty and Reserve/National Guard US servicewomen. (1st August 2015) - Cucciare, Michael A.; Sadler, Anne G.; Mengeling, Michelle A.; Torner, James C.; Curran, Geoffrey M.; Han, Xiaotong; Booth, Brenda M.
Highlights: We examine military characteristics in relation to binge drinking among servicewomen. Deployment to Iraq or Afghanistan (I/A) is associated with binge drinking among active component (AC) and Reserve or National Guard (RNG) servicewomen. Deployment to I/A may be a risk factor for binge drinking among AC servicewomen. Lower military rank may also be a risk factor for binge drinking among AC and RNG servicewomen. Abstract: Background: Prior studies of mostly male U.S. service members suggest service characteristics such as deployment with combat exposure and lower rank may be a risk factor for alcohol misuse. However, these relationships have not been examined among servicewomen who may be at high risk for experiencing deployment-related stressors and associated health consequences. This cross-sectional report of US servicewomen in the Reserve or National Guard (RNG) and active component (AC) sought to examine these associations. Methods: A Midwestern community sample of currently serving and veteran servicewomen ( N = 1339) completed structured telephone interviews. The Generalized Linear Model was used to examine associations between service characteristics, any binge drinking, and frequency of recent binge drinking after adjusting for demographics. Results: After adjusting for demographics, deployment to Iraq or Afghanistan was associated with greater odds of reporting a binge drinking episode, compared to no deployment, among servicewomen in the AC but not RNG. Deployment to Iraq or Afghanistan was also associated with more days binge drinking in both groups compared to servicewomen not deployed. Lower ranking servicewomen also reported higher odds of a binge drinking episode and higher frequency of binge drinking in both the RNG and AC. Conclusions: Service characteristics including deployment to Iraq or Afghanistan (vs. those not deployed) and lower rank (vs. officers) may be a risk factor for recent binge drinking and higher frequency of binge drinking among servicewomen, after adjusting for demographic covariates. Public health and clinical implications are discussed.